2006
DOI: 10.1227/01.neu.0000194834.74873.fb
|View full text |Cite
|
Sign up to set email alerts
|

Management of Cranial Base Chondrosarcomas

Abstract: Because of the intricate nature of the cranial base, a team approach is preferable for managing these challenging lesions. Maximum cytoreductive surgery should be pursued as an initial strategy to minimize neurological injury. Adjuvant stereotactic radiosurgery can be used to treat residual disease or small recurrences. This cohort also illustrates that patients with chondrosarcomas have better long-term survival rates than patients with chordomas of the cranial base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 19 publications
2
38
0
Order By: Relevance
“…4 Even though they are slow growing, chordomas are locally aggressive and their location around the clival region make these lesions particularly challenging to treat. [5][6][7] Optimal results can be achieved with surgery and radiotherapy, but chemotherapy has a limited role. Complete surgical excision is rarely possible and post-resection radiation enhances local control of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…4 Even though they are slow growing, chordomas are locally aggressive and their location around the clival region make these lesions particularly challenging to treat. [5][6][7] Optimal results can be achieved with surgery and radiotherapy, but chemotherapy has a limited role. Complete surgical excision is rarely possible and post-resection radiation enhances local control of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, patients present with an extensive history of headaches and symptoms associated with increased intracranial pressure. Histologically, intracranial chondrosarcomas are classified into three subtypes: Well-differentiated (classical type), intermediate (myxoid type) and undifferentiated (mesenchymal type) (10,11). In a review of 192 chondrosarcoma cases by Chandler et al (12), 62% were of the classical subtype, while the mesenchymal and myxoid types accounted for 30 and 8% of cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Rosenberg et al 24 reported 10-year control rates in the range of 98% with adjuvant radiothera-py in patients with chordomas and low-grade chondrosarcomas. Crockard et al 20 and Wanebo et al 21 reported a 5-year survival rate of 93%. We must consider that these results cannot be simply extrapolated to a patient with Maffucci , s syndrome because of the co-morbidities associated to this syndrome.…”
Section: Maffuccimentioning
confidence: 97%
“…Some authors believe it is a congenital mesodermal dysplasia, since both the hemangiomas and dyschondroplasia are mesodermal in origin 29 . It was emphasized that this syndrome is actually mesodermal dysplasia and, as a result, also includes neuroectodermal dysplastic cases associated with pituitary adenoma or glioma.…”
Section: Maffuccimentioning
confidence: 99%